Travel Agencies' Perception of Higher Education Students as a Viable Market - Shanka, Tekle; Taylor, Ruth (Anatolia, 2002)
With the rate of change exponentially affecting the global tourism industry, some sectors such as traditional travel agencies may need to re-define themselves, their product and service offerings and, in particular to re-identify their markets. An area exhibiting significant growth and tourism potential is that of the higher education student market. A research project was undertaken to investigate travel agencies' existing perceptions of university students (hereafter referred to as students) as a viable market. Results from this survey indicate that holiday/leisure travellers are the most significant markets (80%) for travel agencies, with the main products being consumed as international airfare/packaged tour bookings (66%). While the 35-49 year age group of customers contributes 56% for the travel agency business, the student market contribution to the business was less than 3%. Overall, the results indicate that both the current perceived significance of student markets and the potential significance of this market in the future is very low. Detailed analyses of results are discussed and implications are presented.